Pedagogical Practices of Teaching Assistants in Polysynchronous Classrooms: The Role of Professional Autonomy - Greg Mayer; Dia Sekayi (Park University, 2018)
Polysynchronous learning involves the use of educational technologies to enable remote and face-to-face students to simultaneously participate in live classes. This article uses teaching observation and focus group data to explore the perspectives and instructional practices employed by teaching assistants tasked with facilitating polysynchronous classes. This study's findings suggest that without a sufficient knowledge base, community, and structure to facilitate a teaching environment that extended beyond lecturing, the assistants adopted a knowledge transmission perspective. Based on these findings we discuss teaching practices that could be addressed to train and support instruction in polysynchronous environments.